Low attitude despite excellent knowledge in dental students on treating HIV/AIDS patients: Where are we lacking as educators? - Prebha Manickam; Tina Varghese; Leanne Liew Xiao En; Kee Zi Qin; Kong He Xin (Journal of Education and Health Promotion)
Background: To achieve the goal of the Malaysian National Strategic Plan for ending HIV/AIDS by 2030, holistic management of patients with HIV/AIDS is crucial. Dental students are integral part of the workforce in managing these patients. It is pertinent that the dental students have sufficient knowledge and a positive approach towards this disease. Therefore, it is crucial to gain insight into dental students’ knowledge and attitude towards patients with HIV and improve them. The study aims to investigate the effectiveness of a brief educational intervention to improve dental students’ knowledge and attitude towards patients with HIV/AIDS and to analyse the quality of teaching methods based on the results. Materials and Methods: A validated questionnaire consisting of HIV knowledge and attitude items were administered to year 3 and 4 dental students (n = 89) by convenience sampling method. An educational intervention was conducted with the aim of improving awareness and management of patients with HIV/AIDS in dental settings. After three weeks, a post-assessment questionnaire was administered. The effect of the intervention was analysed by paired t-test (P < 0.048) and Pearson correlation test. Results: The mean age of respondents was 22.2 years. Significant improvement in knowledge was seen with mean scores including pre-assessment (76.7%) and post-assessment (87.4%) indicating excellent knowledge scores. Although positive changes in attitude were noticed, they were not statistically significant. Negative correlation between knowledge and attitude was also reported (r = -0.303). Conclusions: Education about HIV/AIDS is considered the most effective method to improve knowledge and attitude. The results demonstrated that the intervention had successfully increased the students’ knowledge and brought in a change attitude where the expected changes were not statistically significant. To bridge this gap between knowledge and attitude, a step ahead of just imparting ‘education’ is required.